The effect of various types of personal protective equipment materials (work clothing) on fatigue in workers exposed to heat - Ati Nurhayati; Pujiono Pujiono (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Tofu production workers are exposed to hot working environments, placing them at increased risk of physiological strain and work-related fatigue. One strategy to minimize these adverse effects is the use of appropriate personal protective equipment (PPE), particularly work clothing made from suitable fabric materials. Objective: This study aimed to analyze the effect of different work clothing materials on the fatigue levels of tofu production workers exposed to hot working environments. Methods: This study employed a quasi-experimental design with a comparative approach and was conducted in 2025 at Tofu Industry X. All six production workers were recruited as respondents using a total sampling technique. The intervention consisted of three types of work clothing made from polyester, cotton, and Chief Value Cotton (CVC), with each type worn for one hour while performing the same work activities. Fatigue levels were assessed using the Fatigue Assessment Scale (FAS). The data were analyzed using one-way analysis of variance (One-Way ANOVA) with a significance level of 0.05. Results: The production room temperature reached 28.9°C, exceeding the recommended workplace temperature standard (24–27°C). The analysis revealed a statistically significant difference in workers' fatigue levels according to the type of work clothing material (p < 0.001). Cotton work clothing resulted in the lowest fatigue scores compared with polyester and CVC. Conclusion: The type of work clothing material significantly affected workers' fatigue levels in hot working environments. Cotton work clothing was the most effective material for reducing fatigue among tofu production workers.